Cosmo and the magic sneeze - Rees, Gwyneth; Hearn, Sam. (London : Macmillan Children's, 2005)
Cosmo, having passed the special test to become a witch-cat like his father, is helping Sybil, a very scary witch, brew a top-secret spell when he begins to suspect her special ingredient is kittens.
Originally published: 2004.
2.9
K-3
Keywords: Witchcraft -- Juvenile fiction; Occult fiction; Witchcraft -- Fiction; Occult fiction; Witchcraft -- Fiction; Occult fiction